2016
DOI: 10.1111/acem.12857
|View full text |Cite
|
Sign up to set email alerts
|

Practice Pattern Variation in the Care of Children With Acute Asthma

Abstract: Objectives: Pediatric asthma is a highly prevalent disease, affecting over 7 million U.S. children and accounting for 750,000 annual emergency department (ED) visits. Guidelines from the National Asthma Education and Prevention Program recommend limited use of chest radiography (CXR), complete blood counts (CBCs), and antibiotics when managing acute exacerbations of asthma. However, studies suggest frequent overutilization of these resources. The objective was to evaluate differences between pediatric and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…These findings are consistent with prior studies that showed rates of radiology studies for children being inversely proportional to pediatric volume and prescribers in pediatric EDs being likely to prescribe systemic corticosteroids in asthma and less likely to utilize radiography . Other differences in care have been documented for pediatric respiratory illnesses, utilization of CT for minor head trauma, and availability of pediatric staffing and equipment . While important, when measured individually, these components of care quality do not provide a comprehensive view of pediatric emergency care.…”
Section: Discussionsupporting
confidence: 84%
“…These findings are consistent with prior studies that showed rates of radiology studies for children being inversely proportional to pediatric volume and prescribers in pediatric EDs being likely to prescribe systemic corticosteroids in asthma and less likely to utilize radiography . Other differences in care have been documented for pediatric respiratory illnesses, utilization of CT for minor head trauma, and availability of pediatric staffing and equipment . While important, when measured individually, these components of care quality do not provide a comprehensive view of pediatric emergency care.…”
Section: Discussionsupporting
confidence: 84%
“…However, only 3% of patients with URIs were seen by resident physicians, suggesting that the vast majority of ED care for these conditions occurs in community EDs. Unfortunately, evidence from pediatric asthma research suggests resource overutilization, lack of guideline adherence, and inappropriate antibiotic use is more common in community, as opposed to academic, EDs . These differences in care occur in spite of the fact that academic settings tend to be in urban areas, serve patients with a higher rate of comorbidities with less access to care and are more likely to be underserved and medically and socially vulnerable .…”
Section: Discussionmentioning
confidence: 99%
“…11 Children seen in general EDs are also more likely to receive unnecessary testing and treatment. 12 Use of asthma pathways can increase adherence to NIH asthma guidelines and improve quality and efficiency of care for children who present to the ED with asthma. 15,16 However, previous studies were performed in academic or pediatric-specific EDs.…”
Section: Discussionmentioning
confidence: 99%